The ancient Uyghur monument Altun Yaruk: discovery, study, and translations - Masimkhanuly, Дукен; Kadyl, Талдаубек; Zhomart, Ертай (Turkic Studies Journal, 2025)
This article examines the history of the discovery and research of the ancient Uyghur wtitten monument Altun Yaruk, dating back to the 10th century CE. Discovered in the late 19th century, it has been studied by Russian, German, British, Chinese, and later French, Turkish, Japanese, Swedish, and Kazakh scholars. Special expeditions were organized to East Turkestan for its study. there are significant gaps in the research on its language, content, transcription, and translations of Altun Yaruk, which require further scholarly investigation. The manuscript was written in ancient Uyghur script and translated into Chinese, Sanskrit, and other ancient languages during the early Middle Ages. Consequently, scholars from the 19th to the 21st centuries primarily work with translated texts, with preserved copies in Saint Petersburg and Berlin, often referred to as the ‘Saint Petersburg’ and ‘Berlin’ versions. This article aims to systematize and summarize the history on Altun Yaruk by Eastern and Western scholars while highlighting translation specifics. To achieve this objective, the authors have analysed sources written in Chinese, Russian, German, English, Turkish and other languages. They have also compiled factual data from international studies of Altun Yaruk and conducted a comparative analysis of the texts. The contributions of early researchers, particularly Russian and European scholars such as S.Malov, W.Radloff, F.Müller, and A.Stein, are given special attention. Malov’s contributions extend beyond mere transcription and translation, he also identified phonetic distinctions in the consonant system of the monument. Müller published the results of his expeditions, including a transcription and German translation, as early as 1908, thus preceding Malov’s work. Additionally, the Japanese and Turkish scholars research, including R.Arat, W.Eberhard, S.Çağatay among others, has made significant contributions to the study of the written record. The article also highlights the achievements of the Chinese Turkologist Geng Shimin, under whose leadership a school of young scholars specializing in Turkic written monuments, including Altun Yaruk, Maitrisimit, and Tang Xuanzang’s Journey to the West was established. Today, Altun Yaruk has been translated into numerous European, Eastern, and Turkic languages, including Kazakh (by G.Aidarov and others). The authors of this article propose a new translation from Chinese into Kazakh.